Motivational orientation and perception of active learning instruction by pre-service language teachers - Halimi, Florentina; Tryzna, Marta; Brunstein, Angela (Frontiers in Psychology, 2024)
This study investigates the impact of active learning instruction on the motivational orientation of pre-service language teachers. The data were collected by using the AGQ-R and the StRIP questionnaire, and analyzed through repeated measures of MANOVAs and correlation coefficient. Pre-service language teachers reported a higher approach goal orientation emphasizing the desire to succeed rather than avoidance goal orientation, i.e., the fear of failure. In terms of classroom practices, the participants report having experienced all types of instruction (passive, active, interactive and constructive) in the language education program. Although the pre-service teachers' perception of instruction as passive is preponderant in this study, it does not necessarily point to a higher use of traditional passive lecture and note taking practices. Regardless of the perceived instruction type, the participants' motivation and engagement remain high, as they report high cognitive and emotional engagement, as well as very high participation and low distraction levels.Regarding correlations, motivation, engagement and active instruction are all highly correlated with each other, as highly motivated and engaged individuals tend to benefit more from active instruction than less motivated students, who chiefly rely on passive instruction for academic success. The results of the study may indicate an emergent need for a careful balance between various teaching strategies and approaches in language education programs in particular, and possibly at tertiary level pedagogy in general.